La evangelización y las nuevas condiciones socio culturales. (2021)
This article raises the challenge that plays for evangelization, the new culture so called “postmodernity”. Colombia has lived recently, a cultural situation between modernity and premodenity society. In this context the gospel and the church carried mission was announced out and her tasks. This culture is in a process of change, and evangelisters must recognize as well in order to carry of inculturation out the Gospel and the faith; this is the way to be a believer an a significant to the christian message.